2019
DOI: 10.1111/anu.12952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary lipids on growth, body composition and lipid metabolism‐related enzymes and genes in juvenile largemouth bass, Micropterus salmoides

Abstract: This study investigates the effects of different lipids on growth, body composition and lipid metabolism of largemouth sea bass fish Micropterus salmoides. A total of 360 juvenile M. salmoides (mean ± SD mass = 33.83 ± 0.15 g) were randomly stocked into 12 tanks of 0.5 m 3 volume for 8 weeks. Four replicates were made in each group, which were fed one of three diets containing fish oil (FO), soybean oil (SO) or lard oil (LO). The weight gain rate and specific growth rate did not differ among the groups (p > 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
5
12
0
Order By: Relevance
“…In other trials, dietary n‐3 to n‐6 ratios of 0.1 have been reported as sufficient for growth, and although the precise fatty acid requirements of LMB remain unknown, it is generally suggested that any dietary needs for EPA/DHA are low and that demands can be satisfied through hepatic conversion of linolenic acid (Yadav et al, 2020). The lack of effect of the three alternative oils, and their blends, on growth, survival and feed conversion, which support the findings of others (Subhadra et al, 2006a; Tidwell et al, 2007; Yun et al, 2013; Zhang, Li, et al, 2019, Zhang, Tan, et al, 2019), illustrates the feasibility of totally excluding FO from LMB diets. It should nevertheless be noted that dietary alternative proteins and oils have been associated with significant changes in various physiological control processes.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In other trials, dietary n‐3 to n‐6 ratios of 0.1 have been reported as sufficient for growth, and although the precise fatty acid requirements of LMB remain unknown, it is generally suggested that any dietary needs for EPA/DHA are low and that demands can be satisfied through hepatic conversion of linolenic acid (Yadav et al, 2020). The lack of effect of the three alternative oils, and their blends, on growth, survival and feed conversion, which support the findings of others (Subhadra et al, 2006a; Tidwell et al, 2007; Yun et al, 2013; Zhang, Li, et al, 2019, Zhang, Tan, et al, 2019), illustrates the feasibility of totally excluding FO from LMB diets. It should nevertheless be noted that dietary alternative proteins and oils have been associated with significant changes in various physiological control processes.…”
Section: Discussionsupporting
confidence: 83%
“…In other trials, dietary n-3 to n-6 ratios of 0.1 have been reported as sufficient for growth, and although the precise fatty acid requirements of LMB remain unknown, it is generally suggested that any dietary needs for EPA/DHA are low and that demands can be satisfied through hepatic conversion of linolenic acid (Yadav et al, 2020). The lack of effect of the three alternative oils, and their blends, on growth, survival and feed conversion, which support the findings of others (Subhadra et al, 2006a;Tidwell et al, 2007;Yun et al, 2013;Zhang, Li, et al, 2019, Zhang, Tan, et al, 2019 oils have been associated with significant changes in various physiological control processes. For example, increased oxygen consumption, elevated pepsin levels, disturbance in various hepatic enzymes, changes in hepatic gene expression profiles, negative impacts on LMB immunity and, inter alia, histopathological effects upon the gut and changes therein to the microbiome have all been detected (e.g., Habte-Tsion et al, 2020;He et al, 2020;Shi et al, 2019;Subhadra et al, 2006a;Zhang, Li, et al, 2019, Zhang, Tan, et al, 2019Zhou et al, 2018;Zhu et al, 2019).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In fish, the muscle is one of main sites of lipid deposition (Nanton et al, 2007). The amounts of muscle lipid and unsaturated fatty acid (UFA) contents in fish reflect the flesh nutritive values and healthcare actions (Zhang et al, 2019). Muscle quality is one of the most important factors affecting consumers’ purchase of fish food (Gatlin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Trachinotus ovatus , Megalobrama amblycephala (Zhang et al, 2018) and Micropterus salmoides (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%